La tipología familiar y su influencia en el rendimiento escolar de los estudiantes del décimo año de educación básica de la unidad educativa anexa a la Universidad Nacional De Loja periodo 2012-2013 - Quinde Quilambaqui, Rosa Isabel (2014)
The investigation titled family typology and its influence on the academic performance of students in the tenth year of primary education unit attached to the National University of Loja period 2012-2013, aims at analyzing the influence of the type family in the academic performance of students. The research is descriptive, which involves the systematic collection and reporting of data to get an idea of how the family typology influences on academic performance of students. In this investigative process used scientific methods, descriptive, synthetic analytical, statistical, inductive and deductive. The technique used was the same survey yielded information on the problem of the two variables of the subject, with the primary results was determined that the family type does not affect school performance as they are nuclear families with appropriate forms of relationship but if there academic problems. The study population is represented by the tenth year students morning section of the educational unit attached to the National University of Loja and the sample comprised 168 students.